Pendampingan dan Edukasi Grammar-Translation Method Bagi Siswa SMP Untuk Meningkatkan Efikasi Diri dalam Belajar Bahasa Inggris - Yuliyanti, Novy; Romadhon, Romadhon (Jurnal Pengabdian Pada Masyarakat METHABDI, 2025)
This community service project addresses the low self-efficacy of junior high school students in learning English, exacerbated by conventional practices that prioritize rote learning over engagement. The program aimed to enhance students' confidence and grammatical competence through a modified GTM approach, integrating mentoring, contextual materials, and collaborative activities. Conducted at SMP YPWKS Cilegon with 38 seventh-grade students, the intervention included three stages: (1) communication and material development, (2) 2-week interactive sessions (pre-test, role-play, bilingual text analysis, post-test), and (3) mixed-method evaluation (statistical analysis, Likert-scale questionnaires). Results showed a significant increase in post-test scores (average +22.3 points, p=0.000), reduced grammatical errors (e.g., tense usage decreased by 43%), and high satisfaction rates (average 4.5/5), particularly regarding mentor support and contextual learning. The project demonstrates that adapting traditional methods with scaffolding and psychosocial support can bridge pedagogical gaps in low-resource settings. Recommendations include extending program duration, integrating digital tools, and expanding collaboration with stakeholders to sustain meaningful outcomes.